PCOS: Causes and treatment - Dadoush, Souad Fareg Mohammd (Journal of medical and pharmaceutical sciences, 2024)
For women, it is the most prevalent hormonal condition. The term refers to the process by which the follicles responsible for ovulation develop into numerous tiny sacs because they are imprisoned just beneath the surface of the ovaries and are unable to release eggs.The brain's pituitary gland secretes the hormones FSH and LH, which regulate when ovulation occurs, in a healthy state. The hormones progesterone and estrogen secreted by the ovary prime the uterus for the egg. The male hormone androgen is also secreted by the ovary.In polycystic ovary syndrome, the ovary secretes high amounts of androgen, a male hormone, and the pituitary gland secretes high amounts of LH. This causes the menstrual cycle to be delayed or skipped, making it difficult to become pregnant and causing acne and increased facial and body hair.The study concluded with a set of results, the most important of which was that the best way to treat polycystic ovary syndrome is to control it by following a healthy lifestyle and taking some medications recommended by your doctor. The study also found that there is an abnormality in the ovarian cells - most likely theca cells - that is the cause. The main cause of polycystic ovary syndrome
Keywords: PCOS; Hyperanrdogenism; insulin resistance; metformin